2012
DOI: 10.1149/1.4717960
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroethylene Carbonate as an Electrolyte Additive for Improving the Performance of Mesocarbon Microbead Electrode

Abstract: Fluoroethylene carbonate (FEC) was used as a kind of film-forming electrolyte additive for lithium-ion battery. The cyclic voltammetry (CV) and electrochemical impedance spectra (EIS) were used to study the influence of FEC additive on the electrochemical properties of mesocarbon microbead (MCMB)/Li cell. The results show that a thin, low-resistive and uniform SEI film was formed on the surface of MCMB electrode, which cause the excellent cyclability of the electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
5
20
0
Order By: Relevance
“…The optimized geometry has a broken bond between atoms C2 and O5, as shown in Figure g. That is also shown in the experiment by Gustafsson and co-workers, and Wang and co-workers, while Nakai and co-workers claimed that the bond between atoms C1 and O6 is broken by reduction . In this study, we found that the C2–O5 broken one is more stable than the C1–O6 broken one by 6.6 kcal/mol (potential energy) and by 6.4 kcal/mol (free energy) in the absence of Li + .…”
Section: Resultssupporting
confidence: 83%
“…The optimized geometry has a broken bond between atoms C2 and O5, as shown in Figure g. That is also shown in the experiment by Gustafsson and co-workers, and Wang and co-workers, while Nakai and co-workers claimed that the bond between atoms C1 and O6 is broken by reduction . In this study, we found that the C2–O5 broken one is more stable than the C1–O6 broken one by 6.6 kcal/mol (potential energy) and by 6.4 kcal/mol (free energy) in the absence of Li + .…”
Section: Resultssupporting
confidence: 83%
“…Therefore, we can assume that constant surface film formation is prevented, as is FEC consumption. On the other hand, the fact that the VC–EMC ratio in the cycled cell is almost similar to that presented in the case of the pristine electrolyte is in agreement with other studies that report on the suppression of the decomposition of other electrolyte components to a minimum due to the presence of FEC in the electrolyte [ 50 , 54 ]. Hence, a high-rate cycling regime is possible with almost no degradation of the electrolyte.…”
Section: Resultssupporting
confidence: 91%
“…This trend is generally followed by the fluorinated ethylene carbonates (F-ECs), but not by EC, which shows a bond-breaking mechanism exclusively on Li(110) with the presence of LiPF 6 (Figure d). This discrepancy from the trend can be rationalized by the small reductive potential of EC compared to that of F-ECs (0.6 V versus Li/Li + for EC in mesocarbon microbeads/Li electrodes compared to 1.0 V versus Li/Li + for FEC), which makes EC more responsive to the subtle changes in the coordination environment (or work function) on the Li surface.…”
Section: Discussionmentioning
confidence: 94%
“…FEC degrades more readily on the Li metal surfaces than those conventional base electrolyte solvents, such as EC and diethyl carbonate . The reductive potential of FEC-containing electrolytes is 1.0 V versus Li/Li + compared to 0.6 V versus Li/Li + without FEC (measured in mesocarbon microbeads/Li electrodes with base electrolytes EC/DMC/ethyl methyl carbonate (EMC) 1:1:1 and 1 M LiPF 6 ). Computational studies on the reduction mechanisms involving Si and graphite surfaces , and the reduction within the electrolyte solvent body , are widely available, whereas studies particularly on Li metal surfaces are limited.…”
Section: Resultsmentioning
confidence: 99%